PROMOCIÃ“N DE UNA CULTURA PREVENTIVA ANTE DESASTRES NATURALES, DESDE UN ENTORNO DE APRENDIZAJE MEDIADO POR LAS TECNOLOGÃAS - Francisca, GrimÃ³n; Mirella, Herrera; Dinarle, Ortega; MarÃa, Guevara; Elluz, UzcÃ¡tegui (European Scientific Journal, ESJ, 2014)
The population growth in the urban centers has resulted in largeconcentrations of people, at places not apt and vulnerable to risks associatedto natural disasters. Against this background, it is essential promoting aculture of prevention of natural disasters, enhanced by the use of ICT inorder to provide solutions to emergency situations The goal: Develop aculture of prevention in the field of risk management for natural disastersmediated by technologies in ENB: BÃ¡rbula I Naguanagua, Carabobo StateBolivarian Republic of Venezuela. The investigation methodology is actionresearchand the double life cycle is employed to address pedagogical issuesand incorporate them into the software development process for Web-basedlearning. The results are shown on instantiation of double life cycle on thesubject of risk management for children 5th and 6th grade as well asteachers, parents or guardians, and Carabobo Civil Protection personnel. Theapplication presented three versions: Offline installed for Canaimitas, onlineversion installed at a server in Multimedia Laboratory of the CaraboboUniversity and a mobile version. Users were trained in ICT and the virtualclassroom. Also they evaluated the products and gave us the feedback toconform the first version of the software. In conclusion, it is evident the needfor a preventive culture supported in the use of ICTs as an opportunity toraise community awareness, integrating human effort and technological andpedagogical innovation.